Absorption coefficients by coloured dissolved organic matter at 443 nm from a global in-situ collection of open ocean, coastal and inland surface waters matched to Ocean Land Colour Instrument - Bracher, Astrid; Soppa, Mariana A; Banks, Andrew C; Xi, Hongyan; Chaikalis, Spyros; Pitta, Elli; Röttgers, Rüdiger; Zeri, Christina (PANGAEA, 2025)
This in situ data set of absorption coefficients by coloured dissolved organic matter at band centred at 442.5 nm (aCDOM(443)), note: for brevity the band is named 443) consists of different data sets gathered together from measurements collected in open, coastal, and inland surface waters spread around the globe and covering the time from first data delivery by Ocean Land Colour Imager (OLCI) on Sentinel-3A (S3A) in May 2016 until November 2022 which were matched to OLCI on S3A and S3B and used in the paper by Bracher et al. (2025). We only used the absorption coefficient data derived from measurements on discrete water samples to ensure a similar method procedure followed and a similar uncertainty. It includes publicly available data and newly collected, measured and analysed data sets from the Phytooptics group at the Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research (AWI, PI: Astrid Bracher) and Hellenic Centre for Marine Research (HCMR, PI: Andrew C. Banks). This collection was matched that in situ data points had to fall within the 3x3 OLCI FR pixel box and a time window of + 12 hours which followed established community protocols (IOCCG 2018, IOCCG 2019) and particularly EUMETSAT's OLCI matchup protocol (EUMETSAT 2022). Firstly, a pre-processing for quality control and a conversion of the considered in situ data to a common format following Valente et al. (2022) was performed. We flagged and disregarded the following data from the final quality-controlled data set which had (1) unrealistic or missing date or geographic coordinate fields, (2) poor quality (e.g., original flags) or method of observation that did not meet the criteria for the dataset (e.g., not defined in the community protocols (IOCCG 2018, 2019a), and (3) spuriously high or low data. For the last item, the following limits were imposed: [0.0001–10] m−1 for aCDOM(443). OLCI pixels were discarded when flagged with the recommended flags in (EUMETSAT 2022), and the remaining matchups were only considered valid if more than 50% of satellite pixels were available at remote sensing reflectance centred at band 560 nm (Rrs(560), e.g., 5 out of 9 for the 3x3 criterion) per an in situ data point, and a coefficient of variation <0.2. Dedicated matchup software developed by EUMETSAT was used to ensure that the validation process followed the established guidelines, ThoMaS (the Tool to generate Matchups of OC products with S3 OLCI https://gitlab.eumetsat.int/eumetlab/oceans/ocean-science-studies/ThoMaS). In situ data from AODN-2 and Lehmann22 (see description of specific datasets below) were already provided at the nominal OLCI band 443 nm. All other aCDOM(λ) data were provided in hyperspectral resolution (1nm, 2nm or around 3.3 nm resolution). Following Zibordi et al. (2023), these hyperspectral absorption coefficients were transformed to the nominal OLCI bands by averaging over the specific bandwidth. The OLCI matchup data, based on their associated RRS data at the first eight OLCI bands, were assigned to the specific optical water classes (OWCs) according to the Mélin & Vantrepotte (2015) classification. This contains 17 OWCs which range from very turbid to (OWC 1) oligotrophic to very clear waters (OWC 17). The OWC is also delivered for each matchup point (if the assignment fails the field contains "NaN". We provide also for OLCI the standard deviation of the OLCI matchup data to a in situ data point within the 3x3 pixels. For the in situ data we provide the estimate of the uncertainty for each matchup point further described in Bracher et al. (2025).
Keywords: absorption coefficient; coloured dissolved organic matter (CDOM); In situ; matchups; Ocean Land Colour Instrument; optical water classification